2019
DOI: 10.3389/fgene.2019.00632
|View full text |Cite
|
Sign up to set email alerts
|

In Silico Genome-Wide Analysis of the Pear (Pyrus bretschneideri) KNOX Family and the Functional Characterization of PbKNOX1, an Arabidopsis BREVIPEDICELLUS Orthologue Gene, Involved in Cell Wall and Lignin Biosynthesis

Abstract: Stone cells are a characteristic trait of pear fruit, but the contents and sizes of stone cells negatively correlate with fruit texture and flavor. Secondary cell wall thickening and lignification have been established as key steps of stone cell development. KNOTTED-LIKE HOMEOBOX (KNOX) proteins play important roles in plant cell growth and development, including cell wall formation and lignification. Although the characteristics and biological functions of KNOX proteins have been investigated in other plants,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
33
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 34 publications
(35 citation statements)
references
References 43 publications
2
33
0
Order By: Relevance
“…The members of the WOX class have a derived function of stem cell control besides embryonic patterning, stem cell maintenance, and organ formation, indicating that gene amplification followed by functional diversification is a major force in their evolution [19,20]. The TALE (three-amino acid loop extension) class (BEL and KNOX) is characterized by three extra residues between helix 1 and helix 2 [6,21], among which KNOX plays important roles in plant cell growth and development, including cell wall formation and lignification [22,23]. Moreover, studies in Arabidopsis and the peach have shown that AtBP and PpKNOPE1 can interact with the typical KNOX DNA-binding site (TGACAGC) in 4CL, COMT, and LAC to regulate their expression during lignification [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…The members of the WOX class have a derived function of stem cell control besides embryonic patterning, stem cell maintenance, and organ formation, indicating that gene amplification followed by functional diversification is a major force in their evolution [19,20]. The TALE (three-amino acid loop extension) class (BEL and KNOX) is characterized by three extra residues between helix 1 and helix 2 [6,21], among which KNOX plays important roles in plant cell growth and development, including cell wall formation and lignification [22,23]. Moreover, studies in Arabidopsis and the peach have shown that AtBP and PpKNOPE1 can interact with the typical KNOX DNA-binding site (TGACAGC) in 4CL, COMT, and LAC to regulate their expression during lignification [24,25].…”
Section: Introductionmentioning
confidence: 99%
“…Whether it is consistent with KNOX regulation of Arabidopsis meristem stems and buds are worth further investigation [59]. Xi Cheng found that in pear plants co-expressing KNOX and PbKNOX1 these factors are involved in cell wall thickening and lignin biosynthesis, with inhibition of key structural genes involved in lignin synthesis [60].…”
Section: Discussionmentioning
confidence: 94%
“…Whether it is consistent with KNOX regulation of Arabidopsis meristem stems and buds is worth further investigation [53]. Xi Cheng found that in pear plants coexpressing KNOX and PbKNOX1, these factors are involved in cell wall thickening and lignin biosynthesis, with inhibition of key structural genes involved in lignin synthesis [54].…”
Section: Discussionmentioning
confidence: 95%